Madrasah Principal Leadership Role in Improving TeachersÔÇÖ Performance - Putri, Sarmi Sinta; Mardison, Safri (Universitas Islam negeri Mahmud Yunus Batusangkar, 2021)
This study aims to describe the role of the madrasah principal in improving teachersÔÇÖ performance. This was a descriptive qualitative study. Observation, interviews, and documentation were used to collect the data. The source of data were the principal and teachers of MTsN 4 Muko-muko. Data were analyzed in two stages: the first stage was preliminary observation and the second stage was the research which included three steps, namely data reduction, data display, and data verification. Trustworthiness data were tested by conducting triangulation. The result indicated that principal leadership in improving the quality of teachersÔÇÖ performance included Discipline Development Supervision Program (PPD), Supervision and Evaluation (SDE) activity, and Learning Program Planning. These findings are the basic of how discipline, supervision, and learning program planning become the indicators of guidance to improve the quality of teachersÔÇÖ performance.┬á ┬á┬á